From Emissions to Efficiency: A Narrative Review on Sustainable Transportation and Logistics - Rauf, Mohamad Iqbal Abdul; Sari, Intan Tenisia Prawita (Sinergi International Journal of Logistics, 2024)
This narrative review explores innovation in green logistics, covering technologies, logistics models, regulations, consumer behavior, and global implementation. It highlights the environmental urgency driving sustainable logistics and identifies key research gaps. Using a systematic method, peer-reviewed articles were analyzed to reveal that technologies like electric vehicles, hydrogen fuel, biodiesel, AI, IoT, and blockchain improve both environmental and operational outcomes. Sustainable models such as multimodal transport, circular logistics, and collaborative distribution reduce emissions and enhance efficiency. The review emphasizes the role of supportive policies, financial incentives, and stakeholder collaboration, with case studies from Germany, China, India, and Malaysia illustrating successful integrated approaches. However, barriers like limited funding, poor infrastructure, and institutional resistance persist. The study calls for cohesive policies, stronger private sector roles, and interdisciplinary research to support the global shift toward sustainable logistics